Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on the Management of Patients With Positional Plagiocephaly: The Role of Repositioning. Issue 5 (November 2016) - Klimo, Paul; Lingo, Patrick Ryan; Baird, Lissa C.; Bauer, David F.; Beier, Alexandra; Durham, Susan; Lin, Alexander Y.; McClung-Smith, Catherine; Mitchell, Laura; Nikas, Dimitrios; Tamber, Mandeep S.; Tyagi, Rachana; et al.
Abstract : BACKGROUND: Plagiocephaly, involving positional deformity of the calvarium in infants, is one of the most common reasons for pediatric neurosurgical consultation. OBJECTIVE: To answer the question: "what is the evidence for the effectiveness of repositioning for positional plagiocephaly?" Treatment recommendations are provided based on the available evidence. METHODS: The National Library of Medicine MEDLINE database and the Cochrane Library were queried using MeSH headings and key words relevant to repositioning as a means to treat plagiocephaly and brachycephaly. Abstracts were reviewed to identify which studies met the inclusion criteria. An evidentiary table was assembled summarizing the studies and the quality of evidence (Classes I-III). Based on the quality of the literature, a recommendation was rendered (Level I, II, or III). RESULTS: There were 3 randomized trials (Class I), 1 prospective cohort study (Class II), and 6 retrospective cohort studies (Class III). Repositioning education was found to be equal to a repositioning device and inferior to a physical therapy program. Five of the 7 cohort studies comparing repositioning with a helmet reported helmets to be better and take less time. CONCLUSION: Within the limits of this systematic review, repositioning education is effective in affording some degree of correction in virtually all infants with positional plagiocephaly or brachycephaly. Most studies suggest that a molding helmet corrects asymmetry more rapidly and to a greater degree than repositioning education. In a Class I study, repositioning education was as effective as repositioning education in conjunction with a repositioning wrap/device. Another Class I study demonstrated that a bedding pillow was superior to physical therapy for some infants. However, in keeping with the American Academy of Pediatrics' warning against the use of soft positioning pillows in the sleeping environment, the Task Force recommends physical therapy over any positioning device. The full guidelines document can be located athttps://www.cns.org/guidelines/guidelines-management-patients-positional-plagiocephaly/Chapter_3 .